Autophagy activation and photoreceptor survival in retinal detachment. (April 2021) - Xiao, Jianhui; Yao, Jingyu; Jia, Lin; Ferguson, Thomas A.; Weber, Sarah; Sundstrom, Jeffrey M.; Wubben, Thomas J.; Besirli, Cagri G.; Zacks, David N.
Abstract: We assess the effect of autophagy inhibition on photoreceptor (PR) survival during experimental retinal detachment (RD) and examine the and examine the relationship between autophagy and the expression of glycolytic enzymes HK2 and PKM2 in the retina. We find that inhibiting autophagy by genetic knock out of the autophagy activator Atg5 in rod PRs resulted in increased apoptotic and necroptotic cell death during RD, demonstrated by elevated terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive cells, caspase 8 activity, transcript levels of Fas receptor and RIPK3 as compared to controls. The absence of autophagy in rods resulted in downregulation of hexokinase 2 and pyruvate kinase muscle isozyme 2 levels. More than 460 proteins were identified by mass spectroscopy in autophagosomes isolated from detached retinas compared with less than 150 proteins identified in autophagosomes from attached retinas. Among various cellular compartments, proteins from cytoskeleton, cytoplasm and intracellular organelles constituted a large portion of increased autophagosome contents. These proteins represent numerous biological processes, including phototransduction, cell-cell signaling, metabolism and inflammation. Our findings suggest that competent autophagy machinery is necessary for PR homeostasis and improving PR survival during periods of nutrient deprivation. Highlights: Knock out of the autophagy activator  Atg5  in rods results in increased cell death during retinal detachment. Absence of autophagy in rods results in downregulation of hexokinase 2 and pyruvate kinase muscle isozyme 2 levels. Over 460 proteins were identified in autophagosomes from detached retinas. Autophagy improves photoreceptor homeostasis, glycolysis and survival during periods of nutritional deprivation.